A low-energy-consumption, high-capacity silicon-carbon negative electrode material and its preparation method and application
The silicon carbon negative electrode material with triple carbon clad layer was prepared through the steps of pickling and chemical vapor deposition, which solved the problems of high energy consumption and low reversible capacity in the prior art, and achieved high capacity and good cycle stability.
Patent Information
- Application Number
- CN202411050970.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-01
AI Technical Summary
The existing metal-silicon alloy etching method to prepare silicon carbon negative electrode materials has problems such as high raw material cost, large acid consumption, long time to completely remove metal, unstable material structure, and low reversible product capacity.
The metal-silicon alloy powder is used to remove part of the metal and obtain porous silicon microspheres, and then primary carbon coating is carried out by chemical vapor deposition, and secondary carbon coating is carried out in the organic carbon source solution to form a silicon-carbon negative electrode material with a triple carbon coating layer.
It reduces energy consumption, improves the electronic conductivity and reversible capacity of silicon-carbon anode material, and enhances the cyclic stability and structural stability of the material.
Smart Images

Figure CN118908218B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a low-energy-consumption, high-capacity silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of various electronic devices and electric vehicles, people have higher and higher requirements for the energy density and cycle life of lithium-ion batteries. The negative electrode material is an important component of the battery. Together with the positive electrode material, it determines the key performance of the lithium-ion battery, such as cycle life, capacity and safety, and has become the focus of research in various countries.
[0003] At present, the most promising method to improve the energy density of lithium-ion batteries is to use high-capacity silicon-carbon negative electrode materials. Silicon has a high theoretical specific capacity (4200mAh g -1 ), low operating voltage and other characteristics have attracted extensive research, and it is abundant in the earth's crust, low in cost and environmentally friendly, making it one of the most promising next-generation lithium-ion battery negative electrode materials.
[0004] The existing silicon-carbon negative electrode materials mainly have the following synthetic process routes: the first grinding silicon-carbon method mainly reduces the expansion effect of the material by reducing the size of silicon to the nanometer level, and buffers the comprehensive volume expansion of the material through the gaps between silicon particles, providing space for volume change and stress release for the material expansion. However, due to the limitation of the mechanical grinding process, the size of silicon particles is still large, easy to agglomerate, and the product performance is poor; the second chemical vapor deposition method is to store silicon through a porous carbon skeleton. First, a polymer material is used to make carbon particles with a porous structure similar to a sponge, and then silane gas is introduced into the pores of the porous carbon particles. The gas is precipitated into silicon nanoparticles dispersed in the pores of the porous carbon through high-temperature pyrolysis. This method has excellent product performance, but the cost of raw materials and equipment is too high; the third is to prepare silicon-carbon negative electrode materials through metal-silicon alloys, which has the most large-scale application prospects. First, all the metals in the alloy are removed to obtain a porous silicon framework, and then it is compounded with carbon materials to obtain silicon-carbon negative electrode materials. However, removing all the metals in the metal-silicon alloy consumes a lot of acid, and is time-consuming and labor-intensive. According to the reaction kinetics, it is difficult to remove the last 10wt.% of the metal in the alloy, and the energy consumption is significantly increased.
[0005] In view of the problems of high raw material cost, large acid consumption, long time to completely remove metal, unstable material structure and low reversible capacity of the product in the current metal-silicon alloy etching method for preparing silicon-carbon negative electrode materials, the present invention designs a silicon-carbon negative electrode material with low energy consumption and excellent performance. Summary of the invention
[0006] The present invention provides a low-energy-consumption, high-capacity silicon-carbon negative electrode material and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.
[0007] In order to achieve the above object, an embodiment of the present invention provides a method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material, comprising the following steps:
[0008] S1: Using metal-silicon alloy powder as raw material, removing part of the metal in the metal-silicon alloy powder by pickling to obtain porous silicon microspheres;
[0009] S2: performing a carbon coating on the porous silicon microspheres by chemical vapor deposition to obtain primary carbon-coated porous silicon microspheres; the primary carbon coating layer is located on the inner pore surface (inner pore wall) of the porous silicon and the surface of the porous silicon microspheres;
[0010] S3: dispersing the primary carbon-coated porous silicon microspheres in an organic carbon source solution, stirring to evaporate the solvent, and then pyrolyzing at high temperature to perform secondary carbon coating, wherein the secondary carbon coating is located on the surface of the porous silicon microspheres.
[0011] According to one aspect of an embodiment of the present invention, in step S1, the metal-silicon alloy is at least one of iron-silicon, manganese-silicon, zinc-silicon, nickel-silicon, lead-silicon, and cobalt-silicon, with a particle size of 0.1 to 100 μm and a specific surface area of 0.3 to 10 m 2 g -1 The silicon content in the metal-silicon alloy is 5 to 60wt.%; the acid used for pickling is at least one of sulfuric acid, hydrochloric acid, nitric acid, acetic acid, and oxalic acid, with a concentration of 1 to 50wt.%, and the amount of acid used is 0.5 to 1.5 times the standard amount (the standard amount is the theoretical acid consumption of the metal in the fully reacted alloy).
[0012] According to one aspect of the embodiment of the present invention, in step S1, the temperature is 20-40°C, the pickling time is 3-24 hours, and the residual metal content in the porous silicon microspheres after acid dissolution is 1-50 wt.%.
[0013] According to one aspect of the embodiment of the present invention, in step S1, the pore diameter of the porous silicon microspheres is 10 nm to 10 μm, and the specific surface area is 10 to 1000 m 2 g -1 .
[0014] According to one aspect of an embodiment of the present invention, in step S2, a carbon-containing gas and a carrier gas are introduced into the chemical vapor deposition process; wherein the carbon-containing gas includes at least one of alkanes, alkynes, olefins, benzene rings, carbon monoxide, and carbon dioxide, with a volume concentration of 2 to 40 wt.%; and the carrier gas includes at least one of hydrogen, nitrogen, helium, neon, and argon.
[0015] According to one aspect of the embodiment of the present invention, in step S2, the chemical vapor deposition temperature is 300-1200°C; the thickness of the primary carbon coating layer is 0.2-5 μm; the pore diameter of the primary carbon-coated porous silicon microspheres is 10 nm-2 μm, and the specific surface area is 10-500 m 2 g -1 By controlling the reaction time, the pores of the porous silicon microspheres will not be completely occupied by the deposited carbon. After the first carbon deposition, the silicon microspheres will still have a porous structure. The existence of the pores can reserve space for silicon expansion and alleviate the volume effect of the silicon-carbon negative electrode material.
[0016] According to one aspect of an embodiment of the present invention, in step S3, the organic carbon source solution includes an organic carbon source and a solvent, and the viscosity is 1 to 10000 mPa·s; the organic carbon source is at least one of glucose, sucrose, citric acid, cellulose, dopamine salt, formaldehyde, phenolic resin, xylenol, resorcinol, polyacrylonitrile, polypyrrole, polyaniline, and polythiophene, and the concentration is 5 to 70 wt.%; the solvent is at least one of water, ethanol, and acetone. Preferably, in order to ensure that the organic carbon source is only coated on the surface of the porous silicon microspheres and does not enter the pores, the concentration of the organic carbon source is 15 to 50 wt.%, and the viscosity of the organic carbon source solution is 100 to 2000 mPa·s.
[0017] According to one aspect of the embodiment of the present invention, in step S3, the pyrolysis temperature is 600-1200° C.; and the thickness of the secondary carbon coating layer is 0.01-4 μm.
[0018] Based on an overall concept of the invention, an embodiment of the present invention provides a low-energy consumption, high-capacity silicon-carbon negative electrode material obtained by the above-mentioned preparation method, with a silicon content of 20 to 60 wt.%, and a reversible capacity of 800 to 2400 mAh g -1 While the external organic carbon source is pyrolyzed, the undissolved transition metal elements in the silicon can catalyze the graphitization of the first deposited carbon, and a graphite coating layer is formed between the pore wall of the porous silicon microspheres and the first deposited carbon, and finally a silicon-carbon negative electrode material with a triple carbon coating layer is obtained.
[0019] An embodiment of the present invention also provides a low-energy consumption, high-capacity silicon-carbon negative electrode material obtained by the above-mentioned preparation method or the use of the above-mentioned low-energy consumption, high-capacity silicon-carbon negative electrode material in a lithium-ion battery.
[0020] The above scheme of the present invention has the following beneficial effects:
[0021] (1) The acid dissolution process of the present invention controls the amount of acid used and partially retains the transition metal in the alloy, thereby achieving three purposes at the same time: first, reducing energy consumption. According to reaction kinetics, if the metal is to be completely removed, the acid consumption is large and it is time-consuming and labor-intensive; second, the undissolved metal can improve the electronic conductivity of the silicon-carbon negative electrode material, and the metal silicon alloy can reversibly deintercalate lithium as an alloy negative electrode, providing reversible capacity; third, the residual transition metal plays a role in catalyzing graphitization.
[0022] (2) The transition metal remaining in the porous silicon can catalyze the graphitization of the first chemical vapor deposited carbon coating during the second step of pyrolysis of the organic carbon source, and regenerate a layer of graphite coating between the amorphous carbon and the porous silicon pore wall. This coating has better conductivity and mechanical strength. The two-step treatment results in a triple carbon coating structure, which can firmly wrap the silicon particles during charging and discharging, and play a good protective role in isolating the silicon from direct contact with the electrolyte, and can also prevent the porous silicon from breaking during the charging and discharging process. This multiple protection structure gives the material a higher reversible capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is a SEM image of porous silicon after acid dissolution of metal silicon alloy powder according to an embodiment of the present invention;
[0025] Figure 2 It is a cycle performance diagram of the silicon-carbon negative electrode material prepared in Example 3 of the present invention and Comparative Example 3. DETAILED DESCRIPTION
[0026] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0027] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0029] In view of the existing problems, the present invention provides a method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material, comprising the following steps:
[0030] S1: Using metal-silicon alloy powder as raw material, removing part of the metal in the metal-silicon alloy powder by pickling to obtain porous silicon microspheres;
[0031] S2: performing a carbon coating on the porous silicon microspheres by chemical vapor deposition to obtain primary carbon-coated porous silicon microspheres; the primary carbon coating layer is located on the inner pore surface (inner pore wall) of the porous silicon and the surface of the porous silicon microspheres;
[0032] S3: dispersing the primary carbon-coated porous silicon microspheres in an organic carbon source solution, stirring to evaporate the solvent, and then pyrolyzing at high temperature to perform secondary carbon coating, wherein the secondary carbon coating is located on the surface of the porous silicon microspheres.
[0033] According to one aspect of an embodiment of the present invention, in step S1, the metal-silicon alloy is at least one of iron-silicon, manganese-silicon, zinc-silicon, nickel-silicon, lead-silicon, and cobalt-silicon, and the silicon content in the metal-silicon alloy is 5 to 60 wt.%, the particle size is 0.1 to 100 μm, and the specific surface area is 0.3 to 10 m 2 g -1 The acid used for pickling is at least one of sulfuric acid, hydrochloric acid, nitric acid, acetic acid, and oxalic acid, with a concentration of 1 to 50 wt.%, and the amount of acid used is 0.5 to 1.5 times the standard amount (the standard amount is the theoretical acid consumption of the metal in the fully reacted alloy).
[0034] According to one aspect of the embodiment of the present invention, in step S1, the temperature is 20-40°C, the pickling time is 3-24 hours, and the residual metal content in the porous silicon microspheres after acid dissolution is 1-50 wt.%.
[0035] According to one aspect of the embodiment of the present invention, in step S1, the pore diameter of the porous silicon microspheres is 10 nm to 10 μm, and the specific surface area is 10 to 1000 m 2 g -1 .
[0036] According to one aspect of an embodiment of the present invention, in step S2, a carbon-containing gas and a carrier gas are introduced into the chemical vapor deposition process; wherein the carbon-containing gas includes at least one of alkanes, alkynes, olefins, benzene rings, carbon monoxide, and carbon dioxide, with a volume concentration of 2 to 40 wt.%; and the carrier gas includes at least one of hydrogen, nitrogen, helium, neon, and argon.
[0037] According to one aspect of the embodiment of the present invention, in step S2, the chemical vapor deposition temperature is 300-1200°C; the thickness of the primary carbon coating layer is 0.2-5 μm; the pore diameter of the primary carbon-coated porous silicon microspheres is 10 nm-2 μm, and the specific surface area is 10-500 m 2 g -1By controlling the reaction time, the pores of the porous silicon microspheres will not be completely occupied by the deposited carbon. After the first carbon deposition, the silicon microspheres will still have a porous structure. The existence of the pores can reserve space for silicon expansion and alleviate the volume effect of the silicon-carbon negative electrode material.
[0038] According to one aspect of an embodiment of the present invention, in step S3, the organic carbon source solution includes an organic carbon source and a solvent, and the viscosity is 1 to 10000 mPa·s; the organic carbon source is at least one of glucose, sucrose, citric acid, cellulose, dopamine salt, formaldehyde, phenolic resin, xylenol, resorcinol, polyacrylonitrile, polypyrrole, polyaniline, and polythiophene, and the concentration is 5 to 70 wt.%; the solvent is at least one of water, ethanol, and acetone. Preferably, in order to ensure that the organic carbon source is only coated on the surface of the porous silicon microspheres and does not enter the pores, the concentration of the organic carbon source is 15 to 50 wt.%, and the viscosity of the organic carbon source solution is 100 to 2000 mPa·s.
[0039] According to one aspect of the embodiment of the present invention, in step S3, the pyrolysis temperature is 600-1200° C.; and the thickness of the secondary carbon coating layer is 0.01-4 μm.
[0040] Based on an overall concept of the invention, an embodiment of the present invention provides a low-energy consumption, high-capacity silicon-carbon negative electrode material obtained by the above-mentioned preparation method, with a silicon content of 20 to 60 wt.%, and a reversible capacity of 800 to 2400 mAh g -1 While the external organic carbon source is pyrolyzed, the undissolved transition metal elements in the silicon can catalyze the graphitization of the first deposited carbon, and a graphite coating layer is formed between the pore wall of the porous silicon microspheres and the first deposited carbon, and finally a silicon-carbon negative electrode material with a triple carbon coating layer is obtained.
[0041] An embodiment of the present invention also provides a low-energy consumption, high-capacity silicon-carbon negative electrode material obtained by the above-mentioned preparation method or the use of the above-mentioned low-energy consumption, high-capacity silicon-carbon negative electrode material in a lithium-ion battery.
[0042] The following will describe the invention through specific embodiments.
[0043] Example 1
[0044] A method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material comprises the following steps:
[0045] (1) Nickel-silicon alloy powder was used as raw material, and the silicon content was 40 wt.%. The amount of acid used in acid dissolution was 0.9 times the standard amount, and the reaction was not heated. The reaction time was 12 h, and part of the metal in the powder was removed to obtain porous silicon microspheres, in which the nickel content was 20 wt.%, the pore diameter was 500 nm, and the specific surface area was 300 m 2 g -1Compared with completely removing metallic nickel, this acid dissolution process reduces acid consumption by 60%, reduces reaction time by 50%, and does not require heating, which greatly reduces acid dissolution energy consumption and reduces waste liquid volume.
[0046] (2) The acid-washed porous silicon microspheres were subjected to a first carbon coating treatment by chemical vapor deposition, with methane as the carbon source, nitrogen as the carrier gas, and a pyrolysis temperature of 700° C. The reaction time was controlled to obtain a first carbon coating layer with a thickness of 100 nm.
[0047] (3) A second carbon coating treatment was carried out by a liquid phase method, with sucrose as the organic carbon source, water as the solvent, and a pyrolysis temperature of 900°C. The amount of sucrose was controlled to obtain a secondary carbon coating layer with a thickness of 1 μm. At the same time, internal catalytic graphitization was performed to obtain a triple carbon-coated silicon-carbon negative electrode material with a silicon content of 60 wt.%.
[0048] The surface density of silicon-carbon anode is 2 mg cm -2 , the electrolyte solute is LiPF 6 The solvents are EC, DMC, and DEC, the volume ratio is 0.3:0.3:0.4, and the concentration of the solute is 1 mol L -1 . Perform half-battery test, charge and discharge test between 0.01 and 1.5 V (at a current density of 50 mAg -1 The first three charge and discharge tests were carried out at a current density of 200 mAg -1 The electrochemical performance is shown in Table 1.
[0049] Example 2
[0050] A method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material comprises the following steps:
[0051] (1) Using iron-silicon alloy powder as raw material, the silicon content is 50wt.%; the amount of acid used in acid dissolution is 1.3 times the standard amount, heating at 40°C, the reaction time is 14h, and part of the metal in the powder is removed to obtain porous silicon microspheres, in which the iron content is 10wt.%, the pore diameter is 1μm, and the specific surface area is 350m 2 g -1 Compared with completely removing metallic iron, the acid consumption in this acid dissolution process is reduced by 30%, the reaction time is reduced by 40%, and the heating temperature is relatively low, at 40°C, which greatly reduces the energy consumption of acid dissolution and reduces the amount of waste liquid.
[0052] (2) The acid-washed porous silicon microspheres were subjected to a first carbon coating treatment by chemical vapor deposition, with methane as the carbon source, nitrogen as the carrier gas, and a pyrolysis temperature of 900° C. The reaction time was controlled to obtain a first carbon coating layer with a thickness of 300 nm.
[0053] (3) A second carbon coating treatment was carried out by a liquid phase method, with sucrose as the organic carbon source, water as the solvent, and a pyrolysis temperature of 1000°C. The amount of sucrose was controlled to obtain a secondary carbon coating layer with a thickness of 2 μm. At the same time, internal catalytic graphitization was performed to obtain a triple carbon-coated silicon-carbon negative electrode material with a silicon content of 70 wt.%.
[0054] The surface density of silicon-carbon anode is 2 mg cm -2 , the electrolyte solute is LiPF 6 The solvents are EC, DMC, and DEC, the volume ratio is 0.3:0.3:0.4, and the concentration of the solute is 1 mol L -1 . Perform half-battery test, charge and discharge test between 0.01 and 1.5 V (at a current density of 50 mAg -1 The first three charge and discharge tests were carried out at a current density of 200 mA g -1 The electrochemical performance is shown in Table 2.
[0055] Example 3
[0056] A method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material comprises the following steps:
[0057] (1) Manganese-silicon alloy powder was used as raw material, and the silicon content was 60wt.%; the amount of acid used during acid dissolution was 1.5 times the standard amount, heated at 35°C, and the reaction time was 20h. Part of the metal in the powder was removed to obtain porous silicon microspheres, in which the manganese content was 5wt.%, the pore diameter was 2μm, and the specific surface area was 250m 2 g -1 Compared with the complete removal of metallic manganese, the acid consumption of this acid dissolution process is reduced by 35%, the reaction time is reduced by 30%, and the heating temperature is relatively low, at 35°C, which greatly reduces the energy consumption of acid dissolution and reduces the amount of waste liquid.
[0058] (2) The acid-washed porous silicon microspheres were subjected to a first carbon coating treatment by chemical vapor deposition, with methane as the carbon source, nitrogen as the carrier gas, and a pyrolysis temperature of 700° C. The reaction time was controlled to obtain a first carbon coating layer with a thickness of 500 nm.
[0059] (3) A second carbon coating treatment was carried out by a liquid phase method, with sucrose as the organic carbon source, water as the solvent, and a pyrolysis temperature of 1100°C. The amount of sucrose was controlled to obtain a secondary carbon coating layer with a thickness of 1.5 μm. At the same time, internal catalytic graphitization was performed to obtain a triple carbon-coated silicon-carbon negative electrode material with a silicon content of 80 wt.%.
[0060] The surface density of silicon-carbon anode is 2 mg cm -2 , the electrolyte solute is LiPF 6The solvents are EC, DMC, and DEC, the volume ratio is 0.3:0.3:0.4, and the concentration of the solute is 1 mol L -1 . Perform half-battery test, charge and discharge test between 0.01 and 1.5 V (at a current density of 50 mAg -1 The first three charge and discharge tests were carried out at a current density of 200 mA g -1 The electrochemical performance is shown in Table 3.
[0061] In order to highlight the beneficial effects of the present invention, the following comparative examples are now provided for the embodiments:
[0062] Comparative Example 1
[0063] The second carbon coating pyrolysis temperature in step (3) of Example 1 was changed to 550°C; other experimental conditions were kept the same, and a half-cell was assembled for testing. The test mechanism was the same as that in Example 1. The electrochemical properties of the prepared silicon-carbon negative electrode material are shown in Table 1.
[0064] Table 1 Performance comparison of silicon-carbon negative electrode materials prepared at different second carbon coating pyrolysis temperatures
[0065]
[0066] As can be seen from Table 1, the performance of the silicon-carbon negative electrode material prepared when the second carbon coating pyrolysis temperature is higher is better. At high temperature, the transition metal remaining in the porous silicon can catalyze the graphitization of the first chemical vapor deposition carbon coating layer during the second step of organic carbon source pyrolysis, and regenerate a layer of graphite coating between the amorphous carbon and the porous silicon pore wall. The coating has better conductivity and mechanical strength, so the electrochemical performance of the prepared silicon-carbon negative electrode material is better.
[0067] Comparative Example 2
[0068] Step (1) in Example 2 was changed to control the acid dissolution conditions and completely remove the metal in the alloy. The acid consumption in this process was greatly increased, and the process cost was increased. The other experimental conditions were controlled to be the same, and the half-cell was assembled for testing. The test mechanism was the same as that in Example 2. The electrochemical properties of the prepared silicon-carbon negative electrode material are shown in Table 2.
[0069] Table 2 Performance comparison of silicon-carbon negative electrode materials prepared by porous silicon microspheres with partial and complete metal removal
[0070]
[0071] As can be seen from Table 2, compared with the complete removal of metal, the performance of the silicon-carbon negative electrode material prepared by the porous silicon microspheres after partial removal of the metal is better. The residual metal part inside forms an iron-silicon compound with silicon, which can be used as the negative electrode of the lithium-ion battery and provide capacity for reversible charging and discharging; the remaining part exists as a single substance, which can greatly improve the electronic conductivity of the silicon-carbon negative electrode material, which is beneficial to improving the reversible capacity and cycle retention rate; and the residual transition metal can catalyze the graphitization of the first deposited carbon to obtain a new coating layer, further improving the cycle stability.
[0072] Comparative Example 3
[0073] The carbon coating sequence in Example 3 was changed, the first carbon coating was carried out by liquid phase impregnation method, and the second carbon coating was carried out by chemical vapor deposition method; other experimental conditions were controlled to be the same, and half-cells were assembled for testing. The test mechanism was the same as that in Example 3, and the electrochemical properties of the prepared silicon-carbon negative electrode material were shown in Table 3.
[0074] Table 3 Performance comparison of silicon-carbon negative electrode materials prepared at different second carbon coating pyrolysis temperatures
[0075]
[0076] It can be seen from Table 3 that the performance of the silicon-carbon negative electrode material prepared by changing the carbon coating process sequence deteriorates sharply (see Appendix Figure 2 ). Since the organic carbon source solution used in liquid phase impregnation has a high viscosity, it is difficult to enter the pores of porous silicon and can only achieve surface coating. The subsequent chemical vapor deposition carbon is also difficult to enter the pores of porous silicon and can only continue to carry out surface carbon coating, which makes the internal electron conduction of porous silicon more difficult. Therefore, the prepared silicon-carbon negative electrode material has a large polarization during cycling, a low reversible capacity, and a low capacity retention rate.
[0077] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a low-energy-consumption, high-capacity silicon-carbon negative electrode material, characterized in that: The steps include: S1: Using metal-silicon alloy powder as raw material, removing part of the metal in the metal-silicon alloy powder by pickling to obtain porous silicon microspheres; S2: performing a carbon coating on the porous silicon microspheres by chemical vapor deposition to obtain primary carbon-coated porous silicon microspheres; S3: dispersing the primary carbon-coated porous silicon microspheres in an organic carbon source solution, stirring to evaporate the solvent, and then pyrolyzing at high temperature to perform secondary carbon coating, thereby obtaining; The acid concentration used for pickling is 1 to 50 wt.%, and the amount used is 0.5 to 1.5 times the standard amount; The thickness of the primary carbon coating layer is 0.2 to 5 μm; the pore diameter of the primary carbon coated porous silicon microspheres is 10 nm to 2 μm, and the specific surface area is 10 to 500 m 2 g -1 ; The high-capacity silicon-carbon negative electrode material has a reversible capacity of 800 to 2400 mAh g -1 .
2. The method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material according to claim 1, characterized in that: In step S1, the metal-silicon alloy is at least one of iron-silicon, manganese-silicon, zinc-silicon, nickel-silicon, lead-silicon, and cobalt-silicon, with a particle size of 0.1 to 100 μm and a specific surface area of 0.3 to 10 m 2 g -1 The silicon content in the metal-silicon alloy is 5 to 60 wt.%; the acid used for pickling is at least one of sulfuric acid, hydrochloric acid, nitric acid, acetic acid, and oxalic acid.
3. The method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material according to claim 1, characterized in that: In step S1, the residual metal content after pickling is 1 to 50 wt.%, the temperature is 20 to 40°C, and the pickling time is 3 to 24 hours.
4. The method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material according to claim 1, characterized in that: In step S1, the pore diameter of the porous silicon microspheres is 10 nm to 10 μm, and the specific surface area is 10 to 1000 m 2 g -1 .
5. The method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material according to claim 1, characterized in that: In step S2, carbon-containing gas and carrier gas are introduced into the chemical vapor deposition process; wherein the carbon-containing gas includes at least one of alkanes, alkynes, olefins, benzene rings, carbon monoxide, and carbon dioxide, with a volume concentration of 2 to 40 wt.%; and the carrier gas includes at least one of hydrogen, nitrogen, helium, neon, and argon.
6. The method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material according to claim 1, characterized in that: In step S2, the chemical vapor deposition temperature is 300-1200°C.
7. The method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material according to claim 1, characterized in that: In step S3, the organic carbon source solution includes an organic carbon source and a solvent, and has a viscosity of 1 to 10000 mPa·s; the organic carbon source is at least one of glucose, sucrose, citric acid, cellulose, dopamine salt, formaldehyde, phenolic resin, xylenol, resorcinol, polyacrylonitrile, polypyrrole, polyaniline, and polythiophene, and the concentration is 5 to 70 wt.%; the solvent is at least one of water, ethanol, and acetone.
8. The method for preparing a low-energy-consumption high-capacity silicon-carbon negative electrode material according to claim 1, characterized in that: In step S3, the pyrolysis temperature is 600-1200°C; the thickness of the secondary carbon coating layer is 0.01-4 μm.
9. A low-energy-consumption, high-capacity silicon-carbon negative electrode material obtained by the preparation method according to claim 1, characterized in that: The silicon content is 20 to 60 wt.%.
10. Use of a low-energy consumption, high-capacity silicon-carbon negative electrode material obtained by the preparation method according to any one of claims 1 to 8 or a low-energy consumption, high-capacity silicon-carbon negative electrode material according to claim 9 in a lithium-ion battery.
Citation Information
Patent Citations
Preparation method of silicon-carbon cathode material, silicon-carbon cathode material and lithium ion battery
CN107507972A
Silicon-carbon material, preparation method thereof and lithium battery negative electrode material
CN118173750A
Silicon-carbon-based negative electrode material and preparation method thereof
WO2022126882A1
Silicon composite material, preparation method therefor, negative plate and lithium ion battery
WO2022156152A1